Life Stress Impairs Self-Control in Early Adolescence - Duckworth, Angela L.; Kim, Betty; Tsukayama, Eli (Frontiers in Psychology, 2013)
The importance of self-control to a wide range of developmental outcomes prompted the current investigation of negative life events and self-control in early adolescence. In three prospective, longitudinal studies, negative life events reported by the mother (in Study 1) or child (in Studies 2 and 3) predicted rank-order decreases in self-control over time. In all studies, self-control was measured at two different time points using questionnaires completed by three separate raters, including a classroom teacher who knew the child well and two other raters (parents, caregivers, and/or the child himself/herself). Psychological distress measured in Studies 2 and 3 mediated the deleterious effects of negative life events on self-control. These findings extend prior experimental laboratory research documenting the acute effects of stress on self-control.